Efficiency of physical training of teaching staff at higher educational establishment of the Ministry of Internal Affairs of Ukraine - Bezpaliy S. M. (Kharkov National Pedagogical University, 2012)
The level of physical preparedness, functional state and physical health of teaching staff at higher educational establishment of the Ministry of Internal Affairs of Ukraine has been investigated in the article. 126 officers-instructors with different medical-age groups by age, 30-50 years took part іn research. The level of physical preparedness was definite after results of running on 100 m, pulling up on a cross-beam and running on 1000 m. Functional state and health were determined after a method by G.L. Apanasenco. The insufficient level of endurance and health was set at the officers of all age groups. More than 75% of teaching staff has a health level «below from middle» and «low». The lowest level of physical qualities, functional state and health was fixed at teachers to 40 years. The presence of intercommunication was definite between the results of general physical preparedness of teachers (n=32) and indexes of their functional state, health, and professional preparation (r= -0,844 - 0,768). The conducted researches lead to the necessity of improvement of the operating system of physical training of officers-instructors at higher educational establishment of the Ministry of Internal Affairs of Ukraine by application of facilities of general physical training.